2007
DOI: 10.1158/1055-9965.epi-07-0393
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and Carcinogen Exposure with Smoking of Progressively Reduced Nicotine Content Cigarette

Abstract: Background: Reducing the nicotine content of cigarettes to make them non-addictive has been widely discussed as a potential strategy for tobacco regulation. A major concern with nicotine reduction is that smokers will compensate for reduced nicotine by smoking more cigarettes and/or smoking more intensively, thereby increasing their exposure to tobacco smoke toxins. This study examined whether gradual reduction in nicotine exposure increases exposure to tobacco smoke toxins. Methods: This 10-week longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
156
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(179 citation statements)
references
References 22 publications
23
156
0
Order By: Relevance
“…27,28) Cigarette smoke consists of many chemicals, including nicotine, tar with its many carcinogens, and gaseous compounds including carbon monoxide (CO). 29,30) CO was shown to accumulated in the human body with repeated smoking. 31) Chronic exposure to low levels of CO results in tissue hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…27,28) Cigarette smoke consists of many chemicals, including nicotine, tar with its many carcinogens, and gaseous compounds including carbon monoxide (CO). 29,30) CO was shown to accumulated in the human body with repeated smoking. 31) Chronic exposure to low levels of CO results in tissue hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…While transdermal nicotine helps some smokers quit (eg, Stead et al, 2008), most who use nicotine replacement therapies eventually relapse, partly because they miss the behavioral and sensory aspects of smoking (Rose et al, 2000). Smoking cigarettes that deliver less than conventional doses of nicotine (ie,~1 mg/cigarette) reduce nicotine dependence (Benowitz et al, 2007;Benowitz et al, 2012;Benowitz et al, 2015) and promote smoking cessation when used with transdermal nicotine (Hatsukami et al, 2013). Further, a trial of reduced-nicotine cigarettes delivering~0.05-1.2 mg nicotine in 780 smokers showed decreases in nicotine dependence and cigarette consumption at 6 weeks compared to baseline (Donny et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that a reduction in nicotine content leads on average to minimal compensation and no increased exposure to tobacco smoke toxicants. 19,20 In this secondary analysis we analyzed baseline features of smoking to determine if they predicted those who responded differently to nicotine tapering in a 6-month study of nicotine reduction. We found that those with high nicotine dependence, as assessed by baseline FTCD, maintained differences in smoking behavior by smoking more cigarettes and exhibit greater smoke exposure (CO and PAHs) regardless of RNC level compared to those with low nicotine dependence.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 We are unaware of studies that have examined whether individual factors such as nicotine dependence, genetic factors or rate of metabolism influence compensation when experiencing reduced nicotine availability. The present study addresses whether individual level predictors (i.e., nicotine dependence and rate of nicotine metabolism) influence smoking behavior, and tobacco smoke toxicant exposure in a reduced nicotine content cigarette trial.…”
Section: Introductionmentioning
confidence: 99%